The legitimacy of introducing a simple joint-stock company into the Polish legal order - Ryszkowski, Karol; Witoszek-Kubicka, Aleksandra (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: The paper focuses on the legitimacy of introducing the simple joint-stock company (PSA) into the Polish legal order by referring to the financing of the initial phase of business operations. Describes the issue of capital gap, especially significant for capital-intensive innovative enterprises that have a problem obtaining financing due to high operational risk. The work also shows the importance of choosing capital financing sources due to financial risk and development opportunities. It presents an unconventional solution on raising funds for activities through crowdfunding. The paper attempts to answer questions about the legitimacy of introducing a simple joint-stock company into the Polish legal system and potential benefits and threats from the use of this type of company by startups. Aim: The paper proposes two research aims; verification of the legitimacy of introducing a simple joint-stock company in-to the Polish legal order and presentation of possible impact of the introduction of PSA on the use of crowdfunding as a start-ups financing source. Results: Thanks to the analysis of the acts and the literature on the subject, potential advantages and disadvantages of introducing PSA into the Polish legal system were identified. The authors take the position that combining the features of a limited liability company with a joint stock company may be the legislator’s response to the needs of the startup community.